TINGKAT PENGETAHUAN APOTEKER KOMUNITAS MENGENAI PENGOBATAN ASMA - Amelia Lorensia; Rifaatul Laila Mahmudah; Leonardo Immanuel (Jurnal Ilmiah Ibnu Sina (JIIS): Ilmu Farmasi dan Kesehatan, 2020)
Optimal asthma therapy requires collaboration between patients and pharmacists as health workers. Through pharmacy services, pharmacists have the role of providing education and monitoring asthma therapy. But the level of pharmacist's knowledge will be important in its implementation. This study studies the level of medical knowledge from the community in the city of East Surabaya. The research design used in this study was cross sectional and data collection was carried out through questionnaires from previous studies. The level of knowledge includes 6 domains, namely the domain of pharmacological therapy, etiology and pathophysiology, risk factors, resolution, symptoms, and non-pharmacological therapy. The subject is a pharmacist who practices at a pharmacy in East Surabaya. Data is collected by visiting pharmacies one by one to invite pharmacists from each pharmacy. Interviews were conducted directly with research subjects. In this study descriptive data analysis was performed. The study was conducted from April to June 2019 with 108 people. The results of the study concluded: Most subjects had moderate / standard asthma knowledge (37.96%) and only a small proportion had a high level of knowledge (27.77%). From the questionnaire questions, the lowest domain was in non-pharmacological therapy (94.00) and the lowest value was in the question domain (43.00). Therefore, pharmacists need to increase their knowledge in order to help asthma patients achieve optimal treatment. Keywords: asthma, pharmacist, pharmacy, knowledge